QFHSA Board of Directors Disappointed by Vacancies in 2024 School Board Elections - Quebec Federation of Home and School Associations (QFHSA) (2024)

Résolution 2024-01 : Disponibilité de l’instruction en français - Quebec Federation of Home and School Associations (QFHSA) (2024)

Resolution 2024-01 : French Instruction Availability - Quebec Federation of Home and School Associations (QFHSA) (2024)

Résolution 2024-02 : Les incidences à long terme de l’augmentation des frais de scolarité sur les universités de langue anglaise du Québec - Quebec Federation of Home and School Associations (QFHSA) (2024)

Resolution 2024-02 : The Far-Reaching Effects of Tuition Fee Increases on Québec’s English Universities - Quebec Federation of Home and School Associations (QFHSA) (2024)

Résolution 2024-03 : Liste électorale anglaise permanente pour les élections au sein de conseils scolaires - Quebec Federation of Home and School Associations (QFHSA) (2024)

Resolution 2024-03 : Permanent English Voters’ List for School Board Elections - Quebec Federation of Home and School Associations (QFHSA) (2024)

Résolution 2024-04 : Programme d’alimentation intrascolaire provincial - Quebec Federation of Home and School Associations (QFHSA) (2024)

Resolution 2024-04 : Provincial In-School Food Program - Quebec Federation of Home and School Associations (QFHSA) (2024)

Resolution 2024-05 : Cellphone Ban - Quebec Federation of Home and School Associations (QFHSA) (2024)

Résolution 2024-05 : Interdiction d’utiliser un téléphone cellulaire - Quebec Federation of Home and School Associations (QFHSA) (2024)

It's About Us - Quebec Federation of Home and School Associations (QFHSA) (2024)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2024)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2024)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2024)

What Is a Home & School Association? And What Can It Do for Your School Community? - Quebec Federation of Home and School Associations (QFHSA) (2024)

QFHSA Celebrates Successful Negotiations Regarding Sections of Bill 23 - Quebec Federation of Home and School Associations (QFHSA) (2023)

Some Notes on Quebec Government Laws Restricting Access to English CEGEPS and Proposed Fee Hikes for English Universities in Quebec - Bourhis, Richard Y. (QFHSA & COFFEE-QC & ComECH, 2023)

QFHSA Fall Conference 2023 - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA Board of Directors Shocked at CAQ Attack on McGill, Concordia, and Bishop's - Quebec Federation of Home and School Associations (QFHSA) (2023)

The Provincial Government Makes It Difficult to Offer Praise! - Quebec Federation of Home and School Associations (QFHSA) (2023)

The QFHSA Board of Directors Unanimously Supports the Bill 40 Judgment - Quebec Federation of Home and School Associations (QFHSA) (2023)

2023 QFHSA Awards Banquet - Quebec Federation of Home and School Associations (QFHSA) (2023)

The QFHSA Supports Bill S-251 : An Act to Repeal Section 43 of the Criminal Code (Truth and Reconcilliation Commission of Canada's Call to Action Number 6) - Quebec Federation of Home and School Associations (QFHSA) (2023)

The QFHSA Welcomes the Appointment of a Federal Special Representative on Combatting Islamophobia - Quebec Federation of Home and School Associations (QFHSA) (2023)

The QFHSA Strongly Supports Prime Minister Justin Trudeau's Request to the Supreme Court of Canada to Investigate the Possibility of Regulating the Use of the Notwithstanding Clause - Quebec Federation of Home and School Associations (QFHSA) (2023)

Fostering Great Working Relationships in Your School Community - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-01 : Revoke Bill C-13 - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-02 : Regulate Use of the Notwithstanding Clause - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-03 : Better Develop the New Culture and Citizenship in Québec Program - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-04 : Maintain Sexuality Education as a Separate Program - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-05 : Address the Impact of COVID on Student Learning - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-06 : Support School Employees - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-07 : Ensure the Availability of Bilingual Services by Student Ombudsmen - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-08 : Accomodate Immigrant and Refugee Children - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA Fall Conference 2022 - Quebec Federation of Home and School Associations (QFHSA) (2022)

A Response to C-13 : An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to Other Acts - Quebec Federation of Home and School Associations (QFHSA) (2022)
The passage of Bill 96 - An Act respecting French, the official and common language of Quebec – makes  the protections afforded by the Official Languages Act more important to Québec’s English‐speaking community than ever. This community is not simply an extension of the other English‐speaking  communities of Canada; it is a unique community that is largely bilingual and as diverse inculture and geographical location as it is proud.  The many challenges it faces are not only mostly unaddressed by  Bill C‐13 but likely to be exacerbated by it.
Keywords: Official Language Minority Community (OLMC)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2022)

Statement on Coalition Avenir Québec Government’s Refusal to Budge on Provisions for English-speaking CEGEP Students - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

QFHSA News Bulletin : Statement on the Coalition Avenir Quebec's Refusal to Budge on Provisions for English-speaking CEGEP Students - Quebec Federation of Home and School Associations (QFHSA) (2022)

Statement on the Coalition Avenir Quebec's Refusal to Budge on Provisions for English-speaking CEGEP Students - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News : The News Magazine for Home and School Members - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News : The News Magazine for Home and School Members - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022-01 : Objection à la définition d’anglophones “historiques “ et aux restrictions résultantes à l’admissibilité à recevoir des services en anglais - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-01 : Objection to the Definition of “Historic” Anglophones and the Consequent Restrictions to Eligibility for Services in English - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–02 : Demande de garder la race, la religion et la culture comme thèmes centraux au cours proposé sur la citoyenneté - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-02 : Request to Maintain Race, Religion, and Culture as Central Themes in the Proposed Citizenship Course - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-03 : A Call to Suspend and Amend Law 21 - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–03 : Demande de suspension et de modification de la Loi 21 - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–04 : Demande d’être inclus dans le cadre de futures consultations en tant que partenaires du domaine de l’éducation - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-04 : Request to Be Included in Future Consultations as a Partner in Education - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–05 : Demande de services bilingues par les protecteurs des élèves - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-05 : The Offering of Bilingual Services by Student Ombudsmen - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–06 : Enfants ukrainiens immigrants - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-06 : Immigrating Ukrainian Children - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–07 : Programme de langue anglaise dans les CÉGEP du Québec - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-07 : Quebec English CEGEP Curricula - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-08 : Quebec English CEGEP Admissions Policy - Quebec Federation of Home and School Associations (QFHSA) (2022)

Résolution 2022–08 : Politique d’admission aux CÉGEP de langue anglaise - Quebec Federation of Protestant Home & School Associations (2022)

Énoncé de la part du Conseil d’administration de la Fédération québécoise des associations foyers-écoles (FQAFE) portant sur le projet de loi 96 - Quebec Federation of Home and School Associations (QFHSA) (2021)

Statement on Bill 96 by the Board of Directors of the Quebec Federation of Home and School Associations Inc. (QFHSA) - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-01 : Free French Instruction Services for all Who Request Them - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-02 : Evaluation Improvements, and Investments in School Buildings - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-04 : Request to Revise and Improve the Secondary III and Secondary IV History of Quebec and Canada Curriculum - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-05 : Permanent English Voters' List for School Elections - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-06 : Curriculum Development - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-07 : Addressing the Issue of the Teacher Shortage in Quebec - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021 08 : Environmental Awareness - Quebec Federation of Home and School Associations (QFHSA) (2021)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2021)

Home and School : Advocating for Education : Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2020)

Les élections des écoles anglophones doivent être retardées - Garner, Linton (2020)

The QFHSA Back-to-School Survey : What Our Members Had To Say - Quebec Federation of Home and School Associations (QFHSA) (2020)
The Quebec Federation of Home and School Associations (QFHSA) surveyed its members recently on the Quebec government’s plan to reopen schools this spring. We learned that a small minority of parents (16.74%) plan to send their children back to school when it reopens. Of those who intend to keep their children at home, 65.5% are opting for distance learning; and 30%, home-schooling.

Déclaration sur l'abolition du programme « Éthique et culture religieuse » - Quebec Federation of Home and School Associations (QFHSA) (2020)

Resolution from the Board of Directors of the Quebec Federation of Home and School Associations : Challenge to Law 40 - Quebec Federation of Home and School Associations (QFHSA) (2020)

Statement on the Abolition of the "Ethics and Religious Culture" Programme - Quebec Federation of Home and School Associations (QFHSA) (2020)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)